Sport education seasons - Bulger, Sean M. 1969-; Mohr, Derek J.; Rairigh, Richard M.; Townsend, J.Scott (Human Kinetics, 2006)
This book and CD-ROM package includes 68 complete sessions and lessons for three complete seasons - basketball, soccer, and fitness education - that you can use in their entirety or choose lessons to reinforce your existing program. It also includes more than 150 reproducibles in the book and 400 on the CD-ROM